2021
DOI: 10.3390/ijerph182111455
|View full text |Cite
|
Sign up to set email alerts
|

European Educational Programmes in Health Emergency and Disaster Management: An Integrative Review

Abstract: There is a need for trained health professionals who can swiftly respond to disasters occurring worldwide. Little is known about whether the currently available programmes in disaster management are in line with the recommendations of expert researchers. Our objective was to qualitatively review the characteristics of European educational programmes in health emergency and disaster management and to provide guidance to help improve their curricula. We carried out an integrative review to extract the main chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
1
2
0
2
Order By: Relevance
“…This is in congruence to the results of another study conducted elsewhere among a group of health professionals (12). Long-term training programs with comprehensive curriculum should be included in undergraduate dental courses to strengthen dental professionals' ability while combating any disaster (13). Almost 90% of subjects in the present study agreed in this regard.…”
Section: Discussionsupporting
confidence: 90%
“…This is in congruence to the results of another study conducted elsewhere among a group of health professionals (12). Long-term training programs with comprehensive curriculum should be included in undergraduate dental courses to strengthen dental professionals' ability while combating any disaster (13). Almost 90% of subjects in the present study agreed in this regard.…”
Section: Discussionsupporting
confidence: 90%
“…L'Union européenne a proposé en 2014 un programme éducationnel relatif à la gestion de désastres et de crises appelé « Disaster Training Curriculum ». Ce projet proposait une approche holistique et un programme standardisé pour tous les acteurs potentiels concernés dans la préparation et la gestion d'une situation de crise (8). En Belgique, sur 100 hôpitaux participants, 71 % ont estimé être à risque d'incidents chimiques, biologiques, radiologiques et nucléaires (CBRN).…”
Section: Contexte Et Problématiqueunclassified
“…Previous research also found that nurses with a high education level tend to have good critical thinking skills and decision-making abilities (Chiang et al, 2020). In order to increase the competence of disaster nurses, it is essential that specific disaster modules be included in nurses' formal education (Ranse et al, 2022;Veenema et al, 2019); however, the implementation of the majority of disaster education curricula has not been optimal (Al Harthi et al, 2020;Perpiñá-Galvañ et al, 2021;Ranse et al, 2022). For formal disaster education to be effective, it must be continuous (Perpiñá-Galvañ et al, 2021) and must be a combination of Nurse Media Journal of Nursing, 13(2), 2023, 242 Copyright © 2023, NMJN, e-ISSN 2406-8799, p-ISSN 2087-7811 education, training, and simulation using settings that closely resemble actual conditions (Perpiñá-Galvañ et al, 2021;Ranse et al, 2022).…”
Section: Related Factors Of Nurses' Perception Of Disaster Preparedne...mentioning
confidence: 99%